Where the lost ones go eaudiobook - Bowman, Akemi Dawn (Recorded Books, Inc., 2022)
Eliot Katayama is grieving for Babung, her paternal grandmother who just passed away, and she feels like she's the only one. She's less than excited to move to her new house, which smells like lemons and deception, and she's searching for a sign, any sign, that ghosts are real. Because if ghosts are real, it means she can find a way back to Babung. When Eliot chases the promise of paranormal activity to the presumably haunted Honeyfield Hall, she finds her proof of spirits. But these ghosts are losing their memories, stuck between this world and the next, waiting to cross over. With the help of Hazel, the granddaughter of Honeyfield's owner (and Eliot's new crush), she attempts to uncover the mystery behind Honeyfield Hall and the ghosts residing within. And as Eliot fits the pieces together, she may just be able to help the spirits remember their pasts, and hold on to her grandmother's memory.